FRESH AND MECHANICAL CHARACTERISTICS OF SELF-COMPACTING POLYPROPYLENE FIBER CONCRETE INCORPORATED WITH KAOLIN - Hakas Prayuda; Berkat Cipta Zega; Fanny Monika; Fadillawaty Saleh; Martyana Dwi Cahyati (SINERGI, 2020)
Self Compacting Concrete (SCC) is concrete with high fluidity so that it can flow and fill the spaces in the mold without the compaction process. This study discusses the effect of the adding of kaolin and polypropylene fibers in order to increase the flowability, compressive strength, flexural strength, and tensile strength in self-compacting concrete. The additional material of kaolin was 5%, 10%, and 15% of the cement weight. The polypropylene fibers were 1%, 1.5%, and 2%. The flowability test, which was used, was Table flow, V-Funnel, and L-Box. Compressive strength testing was conducted when the concrete was 7, 14, and 28 days old. The flexural test was performed with a measurement of 150 x 150 x 600 mm as many as 18 specimens tested at the age of 28 days. The results showed that the addition of kaolin and polypropylene fibers met the flowability specifications of self-compacting concrete. The addition of polypropylene can increase the flexural strength and tensile strength of the concrete beam, but cannot increase the compressive strength of self-compacting concrete.